Modified green coke material, and its preparation method and use
Patent Information
- Application Number
- JP2024541735
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-11-04
- Filing Date
- 2023-04-04
- Publication Date
- 2025-02-19
- Estimated Expiration
- 2043-04-04
AI Technical Summary
【0038】 従来技術に対して、本願の実施例は、以下の有益な効果を有する。
Smart Images

Figure 2025504806000001_ABST
Abstract
Description
[Technical field]
[0001] The present application relates to the technical field of graphite preparation raw materials, such as modified green coke materials, and methods for their preparation and use. [Background technology]
[0002] As one of the core components of a battery, the negative electrode material plays an important role in the overall performance of the battery. Among the types of related negative electrode materials, graphite-based materials have the advantages of low charge / discharge plateau, high theoretical lithium insertion capacity, good electrical conductivity, etc., and therefore have become commercialized lithium ion battery negative electrode materials. Natural graphite has the advantages of high specific capacity, low cost, abundant resources, etc., and is therefore widely used in the field of commercial negative electrode materials, but its defects such as poor compatibility with electrolyte, large initial irreversible capacity, and poor charge / discharge multiplication performance directly affect its use in lithium ion batteries with long cycle life and high multiplication performance. Artificial graphite has good compatibility with electrolyte, relatively good cycle and multiplication performance, and is a suitable negative electrode material for power batteries with long cycle life and high multiplication performance.
[0003] Ordinary artificial graphite always uses raw coke material as raw material, but the structure of ordinary raw coke is not fully developed, there are many residual light components, which adversely affect the graphitizability, and the graphitization degree, specific capacity and press density of the graphitized product are low, so it cannot meet the needs of graphite anode material with high energy density. Ordinary raw coke has a high volatile content, usually 4% to 15%, and some raw coke raw materials with high volatile content are prone to agglomeration and even solidification during the heat treatment process, which increases the cost of breaking down and dispersing the agglomeration in the next process.
[0004] For example, CN109748274A discloses a method for preparing a low-cost composite graphite particle negative electrode material. Coke material and asphalt powder are mixed in a mass ratio of 100:1 to 100:20 to obtain a mixed material. The mixed material is put into a graphitization furnace and graphitized to obtain a composite graphitized particle material. The composite graphitized particle material is classified to obtain a classified material. The classified material is sieved and demagnetized to obtain a composite graphite particle negative electrode material. The coke-like material in this document is coke (green coke) before needle coke firing.
[0005] Also, for example, CN111354927A discloses a composite graphite negative electrode material, a lithium ion battery, and its manufacturing method and use. The manufacturing method includes the following steps. S1: Prepare a kneaded product of raw coke powder before calcination, flake graphite powder, graphitization catalyst, and graphitizable binder. The mass ratio of raw coke powder before calcination and flake graphite powder is 1:1.5-1:4, the amount of graphitization catalyst is 0.1-0.8% of the sum of the mass of raw coke powder before calcination and flake graphite powder, and the amount of graphitizable binder is 1-9% of the sum of the mass of raw coke powder before calcination and flake graphite powder. S2: Carbonization treatment. S3: High-temperature catalytic graphitization treatment.
[0006] The graphite raw materials in the above documents all use raw coke as raw material, which to a certain extent cannot meet the needs of graphite negative electrode materials with high energy density, and a graphite material with good comprehensive electrochemical performance cannot be obtained.
[0007] Therefore, how to modify the coke-like raw material of graphite material to improve the performance of the subsequently prepared graphite negative electrode material, such as specific capacity, initial efficiency and press density, has become a technical problem that needs to be solved as soon as possible. Summary of the Invention [Problem to be solved by the invention]
[0008] The following is a general summary of the subject matter described herein that is not intended to limit the scope of the claims.
[0009] The present application provides a modified raw coke material and a preparation method and use thereof. The modified raw coke material of the present application has a large amount of long and thin fiber structure and large area structure in the modified raw coke, effectively reduces volatile content, further removes light components, and eliminates the self-caking property of the raw material, so that the material will not further aggregate in the subsequent heat treatment process for preparing graphite. The modified raw coke material is used to obtain a graphite anode material, which can effectively improve the graphitization degree, specific capacity and press density of the artificial graphite anode, and realize the comprehensive improvement of the performance of the graphite anode material. [Means for solving the problem]
[0010] As a first aspect, an embodiment of the present application provides a modified raw coke material, in which in a polarization structure of the modified raw coke material, the sum of the proportions of a long and thin fiber structure and a wide-area structure is 55 to 99%, and the modified raw coke material has a volatile content of 1% or less and less than 5%.
[0011] The modified raw coke material according to the present invention has a large amount of long and thin fiber structure and wide area structure in the modified raw coke, and the volatile content of the modified raw coke is effectively reduced, light components are further eliminated, and the self-caking property of the raw material is eliminated, so that there is no further aggregation during the heat treatment process for preparing graphite in the subsequent process. The graphite negative electrode material is prepared from the modified raw coke material, and the graphitization degree, specific capacity and press density of the artificial graphite negative electrode are effectively improved, while maintaining the good properties of low expansion and strong charging performance of the raw coke, thereby achieving a comprehensive improvement in the performance of the graphite negative electrode material. If the volatile content of the modified raw coke is too low, below 1%, it means excessive heat treatment, and the heat-treated raw coke has properties similar to those of the calcined coke (e.g., the layer spacing after graphitization becomes small), so that the graphite prepared in the subsequent process is easily expanded during charging and discharging, and its strong charging performance and cycle life are poor. If the volatile content is too high, above 5%, it means that the heat treatment is insufficient, and the crystal growth of the raw coke material is incomplete, which limits the effect of improving the gram capacity and press density of the graphite negative electrode material prepared subsequently.
[0012] For example, the volatile content of the modified green coke material may be 1%, 1.3%, 1.5%, 1.8%, 2%, 2.3%, 2.5%, 2.8%, 3%, 3.3%, 3.5%, 3.8%, 4%, 4.3%, 4.5%, 4.8%, 4.9%, or 4.95%, etc. The sum of the percentages of the long fiber structure and the large area structure may be 55%, 58%, 60%, 63%, 65%, 68%, 70%, 73%, 75%, 78%, 80%, 83%, 85%, 88%, 90%, 93%, 95%, 98%, or 99%, etc.
[0013] Preferably, the Hardgrove Grindability Index of the modified raw coke material is 20-100, such as 20, 25, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, 80, 85, 90, 95 or 100.
[0014] Preferably, the modified green coke material has a volatile content of 2%≦volatile content<5%, such as 2%, 2.3%, 2.5%, 2.8%, 3%, 3.3%, 3.5%, 3.8%, 4%, 4.3%, 4.5%, 4.8%, 4.9% or 4.95%.
[0015] In this application, when the volatile content of the modified raw coke material is 2%≦<5%, it is more favorable for the development of long and thin fiber structure and wide area structure of the raw coke material, so that after the modified raw coke material is graphitized, its gram capacity and press density can be effectively improved, while maintaining the good properties of low expansion and strong charging performance of the raw coke.
[0016] Preferably, the true density of the modified raw coke material is 1.4 to 2 g / cm 3 , e.g. 1.4g / cm 3 , 1.41g / cm 3 , 1.42g / cm 3 , 1.43g / cm 3 , 1.44g / cm 3 , 1.45g / cm 3 , 1.46g / cm 3 , 1.47g / cm 3, 1.48g / cm 3 , 1.49g / cm 3 , 1.5g / cm 3 , 1.6g / cm 3 , 1.7g / cm 3 , 1.8g / cm 3 , 1.9g / cm 3 or 2g / cm 3 etc., 1.4 to 1.5 g / cm 3 It is preferable that:
[0017] In the present application, the modified raw coke material has a true density of 1.4 to 1.5 g / cm 3 In the case where the true density is within the range of 1.5 g / cm, the development of the raw coke crystals can be achieved better. 3 If the true density is too small, the graphite prepared subsequently will be prone to expansion during charging and discharging, resulting in poor deep charging performance and cycle life. If the true density is too small, it will be unfavorable for the development of raw coke crystals, resulting in low gram capacity and press density after graphitization.
[0018] In a second aspect, the present application provides an embodiment comprising: A method for preparing a modified raw coke material is provided, comprising the steps of treating a raw coke material to obtain raw coke particles having a D50 of 0.1-5 mm, and then subjecting the raw coke material to a low-temperature heat treatment to obtain the modified raw coke material.
[0019] The present invention provides a method for modifying raw coke material, and strictly restricts the low-temperature heat treatment of raw coke particles with D50 of 0.1-5 mm. After the low-temperature heat treatment, the medium and short fiber structure in the raw coke can be further developed into a long and fine fiber structure, and the proportion of the long and fine fiber structure and the wide-area structure in the polarized structure can be improved. At the same time, the volatile content can be effectively reduced, the light components can be further eliminated, and the self-caking property of the raw material and the aggregation phenomenon that occurs during the heat treatment of the particles can be eliminated, thereby improving the graphitization degree, specific capacity and press density of the artificial graphite negative electrode material prepared using the modified raw coke material as raw material.
[0020] In the present application, if the D50 of the raw coke particles exceeds 5 mm, the volatile matter is not sufficiently discharged during the low-temperature heat treatment, the crystals are not fully developed, and it is difficult to obtain a modified raw coke material in which the sum of the ratio of the long and thin fiber structure and the ratio of the wide-area structure is 55-99% and the volatile matter is 1%≦<5%. Similarly, if the D50 is less than 0.1 mm, the size is too small during the low-temperature heat treatment, which hinders the development of the crystals during the heat treatment, and it is still difficult to obtain the modified raw coke material.
[0021] For example, the green coke particles may be 0.1 mm, 0.3 mm, 0.5 mm, 0.8 mm, 1 mm, 1.3 mm, 1.5 mm, 1.8 mm, 2 mm, 2.3 mm, 2.5 mm, 2.8 mm, 3 mm, 3.5 mm, 3.8 mm, 4 mm, 4.3 mm, 4.5 mm, 4.8 mm or 5 mm, etc.
[0022] Preferably, the raw coke material comprises any one or a combination of at least two of the following: petroleum coke green coke, needle coke green coke, pitch coke green coke or intermediate phase coke.
[0023] Preferably, the method of treatment includes sieving and / or crushing.
[0024] Preferably, the D50 of the raw coke particles is 0.3-3.0 mm, such as 0.3, 0.5 mm, 0.8 mm, 1 mm, 1.2 mm, 1.3 mm, 1.5 mm, 1.6 mm, 1.8 mm, 2 mm, 2.2 mm, 2.3 mm, 2.5 mm, 2.6 mm, 2.8 mm or 3 mm.
[0025] In the present application, when the raw coke particles have a D50 in the range of 0.3 to 3.0 mm, the gram capacity and press density after graphitization of the modified raw coke can be more effectively improved, while maintaining the good properties of low expansion and strong charging performance of the raw coke.
[0026] Preferably, the temperature of the low-temperature heat treatment is 500 to 900°C, for example, 500°C, 530°C, 550°C, 580°C, 600°C, 630°C, 650°C, 680°C, 700°C, 730°C, 750°C, 780°C, 800°C, 830°C, 850°C, 880°C, or 900°C.
[0027] Preferably, the low-temperature heat treatment time is 2 to 6 hours, such as 2 hours, 3 hours, 4 hours, 5 hours, or 6 hours.
[0028] In this application, if the temperature of the low-temperature heat treatment is too low and the time is too short, the crystal growth and volatile matter discharge cannot be realized well, and the gram capacity and press density of the material after graphitization cannot be effectively improved, whereas if the temperature is too high and the time is too long, the graphite prepared subsequently is likely to expand during the charge and discharge process, resulting in poor high-charge performance and cycle life after graphitization.
[0029] That is, the present invention adjusts and controls the temperature and time of low-temperature heat treatment as well as the D50 of raw coke particles to obtain a modified raw coke material having a sum of the proportions of long and thin fiber structure and large-area structure of 55-99% and a volatile content of 1%≦<5% after graphitization, which maintains the good properties of low expansion and strong charging performance of raw coke, and can significantly improve its graphitization degree, gram capacity and press density.
[0030] Preferably, during the low-temperature heat treatment, the content of oxygen gas is 500 ppm or less, for example, 500 ppm, 450 ppm, 400 ppm, 350 ppm, 300 ppm, 250 ppm, 200 ppm, 150 ppm, 100 ppm, 50 ppm or 0 ppm.
[0031] In the present application, during the low-temperature heat treatment, if the content of oxygen gas is too high, it will cause large burning damage to the material, and even create safety risks, which is disadvantageous to the further graphitization of the modified raw coke.
[0032] As a preferred technical solution, the preparation method includes: The method includes crushing the raw coke material to obtain raw coke particles with D50 of 0.1-5 mm, and then subjecting the raw coke material to low-temperature heat treatment at a temperature of 500-900° C. for 2-6 h to obtain the modified raw coke material.
[0033] As a third aspect, the present embodiment provides a graphite anode material obtained by graphitizing the modified raw coke material according to the first aspect.
[0034] The preparation methods of the artificial graphite negative electrode material according to the present application are all common technical means, i.e., they are feasible in the relevant art, and any method using a coke-like material as one of the raw materials is applicable to the present application, that is, the raw coke modified material according to the present application may be used as all of the raw materials of the artificial graphite negative electrode material, or may be used as one of the raw materials of the artificial graphite negative electrode material.
[0035] Illustratively, the present application provides a process for preparing a graphite anode material using the modified raw coke material of the present application. 1) The modified raw coke is crushed, and the D50 after crushing is 8 to 20 μm. 2) The modified raw coke after the above pulverization is graphitized, and the graphitization temperature is 2500 to 3500°C.
[0036] In step 2), the graphitized material may be further treated before or after graphitization by using methods such as classification, modification, coating, or granulation.
[0037] In a fourth aspect, the present embodiment further provides a lithium ion battery comprising the graphite anode material according to the third aspect. Effect of the Invention
[0038] Compared to the prior art, the embodiments of the present application have the following beneficial effects:
[0039] (1) The modified raw coke material according to the embodiment of the present application has a large amount of long and thin fiber structure and wide area structure in the modified raw coke, and the volatile content is effectively reduced, light components are further eliminated, and the self-caking property of the raw material is eliminated, so that further aggregation does not occur in the subsequent heat treatment process for preparing graphite. A graphite anode material is obtained by preparing the modified raw coke material, and the graphitization degree, specific capacity and press density of the artificial graphite anode are effectively improved, and a comprehensive improvement in the performance of the graphite anode material is realized. In the present application, the volatile content of the modified raw coke material obtained by adjusting and controlling the D50 of the raw coke particles in the preparation process and the temperature and time of the low-temperature heat treatment is 1%≦volatile content<5%, and the true density is in the range of 1.4-2g / cm 3 In this case, the battery using the graphite material obtained by the modified raw coke material as the negative electrode has a gram capacity of 352.1mAh / g or more under 1C, and the lithium deposition of the negative electrode is observed when the battery is charged to 100% SOC at different rates (rates are 1C, 2C, 3C, 4C, 5C, and 6C), and the charging window is 1-5C or more.
[0040] (2) The preparation method according to the embodiment of the present application strictly controls the D50 of the raw coke particles in the modification process, and the temperature and time of the heat treatment, thereby making it possible to obtain a modified raw coke material with excellent performance. The preparation method is simple in operation, does not require complicated processing steps, and is suitable for large-scale production.
[0041] Other aspects may be understood upon reading and understanding the drawings and detailed description. [Brief description of the drawings]
[0042] The drawings are intended to provide an understanding of the technical solutions of the present specification, constitute a part of the specification, and are intended to interpret the technical solutions of the present specification together with the examples of the present specification, but are not intended to limit the technical solutions of the present specification.
[0043] [Figure 1] 1 is a polarized photograph of the modified petroleum coke according to Example 1. [Diagram 2]1 is a polarized photograph of raw petroleum coke (unmodified) according to Comparative Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0044] The technical solution of the present application will be further described below by way of specific embodiments. Those skilled in the art should understand that the above examples are merely intended to aid in understanding the present application, and should not be construed as limiting the present application in any way.
[0045] In one specific embodiment, the present application provides a method for preparing a modified green coke material, comprising the steps of:
[0046] The raw coke material is crushed to obtain raw coke particles with D50 of 0.1-5 mm, and then the raw coke particles are subjected to low-temperature heat treatment at a temperature of 500-900°C for 2-6 hours in an environment with an oxygen gas content of ≦500 ppm to obtain the modified raw coke material.
[0047] However, the raw coke material includes any one or a combination of at least two of petroleum coke green coke, needle coke green coke, pitch coke green coke, or intermediate phase coke.
[0048] Examples 1 to 4 Examples 1 to 4 provide modified petroleum coke materials. The volatile content, Hardgrove grindability index (HGI), true density, and the sum of the proportion of long fine fibers and large area structure in the polarized structure of the modified petroleum coke materials are shown in Table 1.
[0049] Examples 1-4 further provide a preparation method for modified petroleum coke material. The preparation method provided according to a specific embodiment has an oxygen content of less than 500ppm during low-temperature heat treatment, and the volatile content of the original petroleum coke raw material is 10%, and other parameters are shown in Table 1.
[0050] Comparative Example 1 In this comparative example, no treatment is performed on the petroleum coke material.
[0051] Comparative Examples 2 to 6 Comparative Examples 2 to 6 provide modified petroleum coke materials. The volatile content, Hardgrove Grindability Index (HGI), true density, and the sum of the proportion of long fine fibers and broad structure in the polarized structure of the modified petroleum coke materials are shown in Table 1.
[0052] Comparative Examples 2 to 6 further provide the preparation methods of modified petroleum coke materials. The preparation methods provided according to specific embodiments have the following characteristics: the oxygen content in the process of low-temperature heat treatment is less than 500 ppm, the volatile content of the original petroleum coke raw material is 10%, and other parameters are shown in Table 1.
[0053] Fig. 1 shows a polarized photograph of the modified petroleum coke according to Example 1, and Fig. 2 shows a polarized photograph of the original petroleum coke (unmodified) according to Comparative Example 1. As can be seen from a comparison between Fig. 1 and Fig. 2, the long fine fiber texture and the wide-area structure in the low-temperature heat-treated raw coke were obviously improved. From the proportions of the long fine fiber texture and the wide-area structure in the polarized photograph, it was found that the sum of the proportions of the long fine fiber texture and the wide-area structure in the modified raw coke was 55-99%.
[0054] [Table 1]
[0055] The modified or unmodified (Comparative Example 1) petroleum coke materials according to Examples 1 to 4 and Comparative Examples 1 to 6 were used as raw materials for the artificial graphite negative electrode material to prepare the artificial graphite negative electrode material. The preparation process is as follows.
[0056] 1) The modified raw coke is crushed, and the D50 after crushing is 15 μm.
[0057] 2) The modified raw coke after the above pulverization is classified and then graphitized, and the graphitization temperature is 3000℃.
[0058] The modified or unmodified (Comparative Example 1) petroleum coke materials according to Examples 1 to 4 and Comparative Examples 1 to 6 were successively pulverized, classified, and graphitized to obtain artificial graphite negative electrode materials.
[0059] Button batteries were obtained by manufacturing the artificial graphite negative electrode materials according to Examples 1 to 4 and Comparative Examples 1 to 6. The test conditions for gram capacity were room temperature, 1C constant current charge and discharge, and charge and discharge cutoff voltage of 0.005V to 2V. The charging window was the ratio range where no lithium deposition occurred on the negative electrode sheet when the above batteries were charged to 100% SOC at different ratios (1C, 2C, 3C, 4C, 5C, and 6C). The results are shown in Table 2.
[0060] [Table 2]
[0061] As can be seen from the data results of Examples 1 and 4, if the true density was too high, exceeding 1.5, and the volatile content was below 2%, this was detrimental to improving the strong charging performance of the material after graphitization.
[0062] As can be seen from the data results of Example 1 and Comparative Examples 2 to 4, if the raw coke particles before the low-temperature heat treatment in the process of preparing the modified raw coke material are too small (less than 0.1 mm) or too large (more than 5 mm), it is impossible to obtain a modified raw coke material in which the sum of the proportions of the long and thin fiber structure and the wide-area structure is 55 to 99% and the volatile content is 1% or less and less than 5%, and therefore it is impossible to simultaneously improve the gram capacity and strong charging performance of the material after graphitization.
[0063] As can be seen from the data results of Example 1, Comparative Example 5 and Comparative Example 6, in the process of preparing the modified raw coke material, even if the particle size of the raw coke particles is in the range of 0.1 to 5 mm, if the temperature is too low, the improvement of the gram capacity of the material after graphitization is not significant, and if the temperature is too high, the strong charging performance of the material after graphitization is also affected.
[0064] Overall, as can be seen from the data results of Example 1 and Comparative Examples 2 to 6, in the process of preparing the modified raw coke material, the ranges of raw coke particle size, temperature and time must be satisfied simultaneously, and they act synergistically, so that the modified raw coke material expected in the present application can be obtained and the specific capacity of the subsequent artificial graphite negative electrode material can be improved.
[0065] Examples 5 to 9 Examples 5 to 9 provide modified pitch coke materials. The volatile content, Hardgrove grindability index (HGI), true density, and the sum of the proportion of long fine fibers and broad structure in the polarized structure of the modified pitch coke materials are shown in Table 3.
[0066] Examples 5-9 further provide a preparation method for modified pitch coke material. The preparation method provided according to a specific embodiment has an oxygen content of less than 500 ppm during low-temperature heat treatment, and the volatile content of the original pitch coke material is 6%, and other parameters are shown in Table 3.
[0067] Comparative Example 7 In this comparative example, no treatment is performed on the pitch coke material.
[0068] Comparative Examples 8 to 10 Modified pitch coke materials are provided in Comparative Examples 8 to 10. The volatile content, Hardgrove grindability index (HGI), true density, and the sum of the proportion of long fine fibers and broad structure in the polarized structure of the modified pitch coke materials are shown in Table 1.
[0069] Comparative Examples 8 to 10 further provide a preparation method for modified pitch coke material. The preparation method provided according to a specific embodiment has an oxygen content of less than 500 ppm during low-temperature heat treatment, and the volatile content of the original pitch coke raw material is 10%, and other parameters are shown in Table 3.
[0070] [Table 3]
[0071] The modified or unmodified (Comparative Example 1) pitch coke materials according to Examples 5 to 9 and Comparative Examples 7 to 10 were used as raw materials for artificial graphite negative electrode materials, and artificial graphite negative electrode materials were obtained by preparing them. The preparation process is as follows.
[0072] 1) The modified raw coke is crushed, and the D50 after crushing is 15 μm.
[0073] 2) The modified raw coke after the above pulverization is classified and then graphitized, and the graphitization temperature is 3000℃.
[0074] The modified or unmodified (Comparative Example 1) pitch coke materials according to Examples 5 to 9 and Comparative Examples 7 to 10 were successively pulverized, classified, and graphitized to obtain artificial graphite negative electrode materials.
[0075] Button batteries were obtained by manufacturing artificial graphite negative electrode materials according to Examples 5 to 9 and Comparative Examples 7 to 10. Regarding the test conditions, the test conditions for gram capacity were room temperature, 1C constant current charge and discharge, and charge and discharge cutoff voltage of 0.005V to 2V. The charging window was the ratio range in which lithium deposition did not occur on the negative electrode sheet when the above batteries were charged to 100% SOC at different ratios (1C, 2C, 3C, 4C, 5C, and 6C). The results are shown in Table 4.
[0076] [Table 4]
[0077] As can be seen from the data results of Examples 5, 7 and 8, if the true density was too high, exceeding 1.5, and the volatile content was below 2%, this was detrimental to improving the strong charging performance of the material after graphitization.
[0078] As can be seen from the data results of Example 5 and Comparative Example 7, unless any modification treatment is performed on the raw coke material, the short fibers in the raw coke material cannot be further developed into long fibers, and therefore, the gram capacity after graphitization cannot be improved.
[0079] As can be seen from the data results of Example 1 and Comparative Examples 8 to 10, in the process of preparing the modified raw coke material, the three factors of the low-temperature heat treatment temperature, time, and D50 of the raw coke particles must be met simultaneously, and they act synergistically to realize the modification of the raw coke material and further improve the specific capacity of the artificial graphite negative electrode material. If only one of the two factors is met, it will affect the development of the raw coke crystals, and the purpose of improving the gram capacity after graphitization will not be achieved.
[0080] Examples 10 to 13 Examples 10 to 13 provide modified needle coke materials. Table 3 shows the volatile content, Hardgrove Grindability Index (HGI), true density, and the sum of the ratio of long fine fibers and broad structure in the polarized structure of the modified needle coke materials.
[0081] Examples 10 to 13 further provide a preparation method for modified needle coke material. The preparation method provided according to a specific embodiment has an oxygen content of less than 500 ppm during low-temperature heat treatment, and the volatile content of the original needle coke raw material is 6%, and other parameters are shown in Table 5.
[0082] Comparative Example 11 In this comparative example, no treatment is performed on the needle coke material.
[0083] Comparative Examples 12 to 13 Comparative Examples 12 to 13 provide modified needle coke materials. The volatile content, Hardgrove Grindability Index (HGI), true density, and the sum of the ratio of long fine fibers and broad-area structure in the polarized structure of the modified needle coke materials are shown in Table 1.
[0084] Comparative Examples 12-13 further provide a preparation method for modified needle coke material. The preparation method provided according to a specific embodiment has an oxygen content of less than 500 ppm during low-temperature heat treatment, and the volatile content of the original needle coke raw material is 10%, and other parameters are shown in Table 5.
[0085] [Table 5]
[0086] The modified or unmodified (Comparative Example 1) needle coke materials according to Examples 10 to 13 and Comparative Examples 11 to 12 were used as raw materials for artificial graphite negative electrode materials, and artificial graphite negative electrode materials were obtained by preparation. The preparation process is as follows.
[0087] 1) The modified raw coke is crushed, and the D50 after crushing is 15 μm.
[0088] 2) The modified raw coke after the above pulverization is classified and then graphitized, and the graphitization temperature is 3000°C.
[0089] The needle coke materials, which were modified or unmodified (Comparative Example 1) according to Examples 10 to 13 and Comparative Examples 11 to 13, were crushed, classified, and graphitized in this order to obtain artificial graphite negative electrode materials.
[0090] Button batteries were obtained by manufacturing artificial graphite negative electrode materials according to Examples 10 to 13 and Comparative Examples 11 to 12. Regarding the test conditions, the test conditions for gram capacity were room temperature, 1C constant current charge and discharge, and charge and discharge cutoff voltage of 0.005V to 2V. The charging window was the ratio range in which lithium deposition did not occur on the negative electrode sheet when the above batteries were charged to 100% SOC at different ratios (1C, 2C, 3C, 4C, 5C, and 6C). The results are shown in Table 6.
[0091] [Table 6]
[0092] As can be seen from the data results of Examples 10, 12 and 13, if the true density is too high, exceeding 1.5, and the volatile content is below 2%, it is disadvantageous to improve the strong charging performance after graphitization of the modified raw coke.
[0093] As can be seen from the data results of Example 10 and Comparative Example 11, if the raw coke material is not subjected to any modification treatment, the short fibers in the raw coke material cannot be further developed into long fibers, and the volatile matter in the raw coke cannot be discharged, so that the specific capacity of the modified raw coke after graphitization cannot be improved.
[0094] As can be seen from Tables 1 to 6, the modified raw coke material according to the present application can be obtained only because the preparation process must simultaneously satisfy the three conditions of D50 of the raw coke particles, the temperature and time of the low-temperature heat treatment. At the same time, the volatile content of the modified raw coke material is 2%≦volatile content<5% and the true density is in the range of 1.4 to 1.5 g / cm. 3 In this case, the artificial graphite anode material is less likely to aggregate during the subsequent preparation, and the performance of the resulting graphite anode material is better, with a higher specific capacity.
[0095] In summary, the modified raw coke material according to the present application has effectively reduced volatile content, further eliminated light components, and eliminated the self-caking property of the raw material, so that it will not further aggregate during the subsequent heat treatment process for preparing graphite, and the long and thin fiber structure and wide area structure in the modified raw coke are increased, and a graphite anode material is obtained by preparing the modified raw coke material, which can effectively improve the graphitization degree, specific capacity and press density of the artificial graphite anode, thereby achieving a comprehensive improvement in the performance of the graphite anode material. In the present application, the volatile content of the modified raw coke material obtained by adjusting and controlling the D50 of the raw coke particles in the preparation process and the temperature and time of the low-temperature heat treatment is 1%≦volatile content<5%, and the true density is in the range of 1.4-2g / cm 3 In this case, the graphite material obtained by the modified raw coke material is used as the negative electrode of the battery, and the gram capacity at 1C reaches 352.1mAh / g or more. The battery is charged to 100% SOC at different rates (rates are 1C, 2C, 3C, 4C, 5C, 6C) to observe the lithium deposition of the negative electrode, and the charging window is 1-5C or more.
[0096] The applicant declares that the above is only a specific embodiment of the present application, and the scope of protection of the present application is not limited thereto. Those skilled in the art should understand that any modifications or replacements that can be easily conceived within the technical scope disclosed in the present application are all included in the scope of protection and disclosure of the present application.
Claims
1. 1. A modified raw coke material comprising: In the polarization structure of the modified raw coke material, the sum of the ratio of the long and thin fiber structure and the wide-area structure is 55 to 99%, and the volatile content of the modified raw coke material is 1% or less and less than 5%. Modified green coke material.
2. The true density of the modified raw coke material is 1.4 to 2 g / cm 3 and preferably 1.4 to 1.5 g / cm 3 That is, The modified green coke material of claim 1 .
3. The modified raw coke material has a Hardgrove grindability index of 20 to 100; The modified green coke material according to claim 1 or 2.
4. The modified raw coke material has a volatile content of 2%≦<5%; The modified green coke material according to any one of claims 1 to 3.
5. The method includes the steps of treating a raw coke material to obtain raw coke particles having a D50 of 0.1-5 mm, and then subjecting the raw coke material to a low-temperature heat treatment to obtain a modified raw coke material; A method for preparing a modified green coke material.
6. The raw coke material comprises any one or a combination of at least two of petroleum coke green coke, needle coke green coke, pitch coke green coke or intermediate phase coke; A method for preparing the modified green coke material of claim 5.
7. The method of processing includes sieving and / or crushing, A method for preparing the modified green coke material according to any one of claims 5 to 6.
8. The D50 of the raw coke particles is 0.3 to 3.0 mm. A method for preparing the modified green coke material according to any one of claims 5 to 7.
9. The temperature of the low-temperature heat treatment is 500 to 900 ° C., and the time of the low-temperature heat treatment is 2 to 6 h. A method for preparing the modified green coke material according to any one of claims 5 to 8.
10. During the low-temperature heat treatment, the content of oxygen gas is 500 ppm or less. A method for preparing the modified green coke material according to any one of claims 5 to 9.
11. The raw coke material is crushed to obtain raw coke particles with a D50 of 0.1-5 mm, and then the raw coke particles are subjected to low-temperature heat treatment at a temperature of 500-900° C. for 2-6 h under an oxygen gas content of ≦500 ppm to obtain a modified raw coke material; A method for preparing a modified green coke material.
12. 5. A graphitized coke obtained by graphitizing the modified raw coke material according to any one of claims 1 to 4. Graphite anode material.
13. The graphite anode material according to claim 12, Lithium-ion battery.
14. A method for preparing a graphite anode material using the modified raw coke material according to any one of claims 1 to 4, comprising the steps of: (1) crushing the modified raw coke material, so that the D50 after crushing is 8 to 20 μm; (2) graphitizing the modified raw coke material after pulverization, the graphitization temperature being 2500-3500°C; method.
15. (1) treating raw coke material to obtain raw coke particles with D50 of 0.1-5 mm, and then subjecting the raw coke material to low-temperature heat treatment to obtain modified raw coke material; (2) crushing the modified raw coke material, so that the D50 after crushing is 8 to 20 μm; (3) graphitizing the modified raw coke material after pulverization, the graphitization temperature being 2500-3500°C; A method for preparing a graphite anode material.
Citation Information
Patent Citations
Preparation method of carbon nanotube
CN115028161A
Manufacturing method of carbon material for electric double-layer capacitor electrode, and manufacturing method of electric double-layer capacitor using the carbon material
JP2001284188A
Artificial graphite material for lithium ion secondary battery negative electrode, and production method therefor
WO2021256558A1